Increased premature mortality of competitive powerlifters suspected to have used anabolic agents - Pärssinen, M.; Kujala, U.; Vartiainen, E.; Sarna, S.; Seppala, T. (International Journal of Sports Medicine, 2000)
Misuse of supraphysiological doses of anabolic steroids is claimed to have serious side effects. The aim of the study was to determine the mortality, and the cause of premature deaths among a group of subjects who are strongly suspected to have used anabolic steroids for a non-medical purpose over several years. The mortality of 62 male powerlifters placed 1st-5th in weight series 82.5-125 kg in Finnish championships during 1977-1982 was compared with the mortality of population controls. The mortality during the 12-year follow-up was 12.9% for the powerlifters compared to 3.1% in the control population. By 1993 eight of 62 powerlifters and 34 of 1094 population controls had died, thus the risk of death among the powerlifters was 4.6 times higher (95% CI 2.04-10.45; p = 0.0002). The causes of premature death among the powerlifters were suicide (3), acute myocardial infarction (3), hepatic coma (1) and non-Hodgkin's lymphoma (1). These findings add to the growing amount of evidence of an association between anabolic steroid abuse and premature death, and support the view that measures to decrease AAS misuse among both competitive and amateur athletes are justified.